Carbon-energy taxation lessons from Europe - Andersen, Mikael Skou.; Ekins, Paul. (Oxford : Oxford University Press, 2009)
This book offers an extensive analysis of carbon-energy taxation that addresses the interplay between carbon-energy taxation and emissions trading, as well as the implications for future international climate policy.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Carbon taxes -- Europe; Emissions trading -- Europe; Environmental policy -- Economic aspects -- Europe